Effectiveness of Hematoma Block in Term of Pain Relief in Distal Radial Fractures. (Journal of Pakistan Orthopaedic Association, 2025)
Objective: To find out effectiveness of hematoma block in term of pain relief in reduction of distal radius fracture.Methodology: This Cross sectional (descriptive) study was conducted in the Department of Orthopedics Surgery, Lady Reading Hospital, Peshawar from August 19, 2021 till February 18, 2022 on total of 150 patients aged 18-80 years of either gender presented to the emergency department with acute pain and deformity of radius, confirmed at x ray were enrolled using Consecutive non-probability sampling. Study was conducted after approval of hospital ethical committee and written informed consent of patients. Reduction was done using hematoma block and post- procedure VAS was checked to determine effectiveness of hematoma block. Data was entered and analyzed using SPSS 20.Results: In our study total 150 patients were enrolled with mean age of 43.72±17.6 years. There were 49.3% patients from younger age group (18-40 years) and 50.7% from elder age group (41-80 years). There were 64% males and 36% female patients. Hematoma block was effective in 68% patientsConclusion: Hematoma block is effective in reducing pain after reduction of distal radius fracture.